Apoptotic effects of α-Mangostin on cervical cancer cell line / Aisha I. I. El Habbash - Aisha I. I., El Habbash (2018)
α-Mangostin (AM) is a xanthone type of compound which exhibits a promising and diverse pharmacological effects. Several in vitro studies have shown that AM induces apoptosis and cell death in breast cancer cell lines MCF-7 and MDA-MB-231. In this study, the apoptotic and antitumor effects of AM on human cervical cancer cell lines HeLa and Ca Ski were investigated. The cytotoxic properties of AM were evaluated on HeLa (HPV18-containing) and Ca Ski (HPV16-containing) cell lines, as well as on human normal ovarian cell line (SV40), by using MTT assay. The apoptogenic effects of AM on HeLa and Ca Ski cells were assessed using fluorescence microscopy analysis (AO/PI double staining and Hoechst dye). The effect of AM on cell proliferation was also studied through clonogenic assay. ROS production evaluation, flow cytometry (cell cycle) analysis, and multiple cytotoxicity assays were also conducted to determine the mechanism of cell apoptosis involving caspases 3/7, 8, and 9. The cytotoxic effect of AM on cancer cells was higher than normal cells wherein it exhibited low IC50 values on HeLa and Ca Ski cells. Cell shrinkage, membrane blebbing, chromatin condensation, and apoptotic body formation were observed on HeLa and Ca Ski cells. Furthermore, AM induced mitochondrial apoptosis and cell cycle arrest in the G2/M phase in HeLa cells and enhanced S-phase accumulation in Ca Ski cells. The mitochondrial apoptosis was confirmed based on significant increase in the levels of caspases 3/7 and 9 in a dose-dependent manner. By contrast, unaltered caspase 8 levels in both cell lines indicated the non-involvement of an extrinsic pathway in cell death mechanism. Moreover, cytochrome c release from the mitochondria to the cytosol and morphological changes in matrix metalloproteinase-2 (MMP) in HeLa and Ca Ski cells provided iv evidences that AM can induce apoptosis via mitochondrial-dependent pathway and cell cycle arrest. AM exerted a remarkable antitumour effect and induced characteristic apoptogenic morphological changes, which indicated the occurrence of cell death. This study reveals that AM could be a potential anticancer compound for cervical cancer.